Understanding and quantifying the anoxic corrosion of carbon steel in a Swiss L/ILW repository environment. (28th April 2017) - Senior, Nick; Newman, Roger; Wang, Steve; Diomidis, Nikitas
ABSTRACT: The anaerobic corrosion of steel was monitored under simulated Swiss low-/intermediate-level waste repository conditions. Steel was studied both as bare rods and cast in cement, in water vapour, simulating the unsaturated anoxic phase, and during immersion in various pore waters, representative of the saturated phase. All tests were performed at 50°C. Hydrogen evolution from grout, comprising commercial cement and sand, was also studied. Grouted steel specimens initially generated hydrogen that was comparable to grout alone, which was attributed to the presence of iron detritus from the ball-milling of cement clinker. The corrosion rate of immersed test specimens peaked during the first 100 days, likely due to the formation of a passive film. Corrosion rates generally declined to <3 nm/year, although there were several notable exceptions where hydrogen generation was erratic. This was attributed to localised corrosion and may be an important factor to understand when modelling hydrogen generation rates. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems .